O museu Beta: estratégias para um museu sempre contemporâneo - Lorena Melgaço Silva Marques (2011)
Important changes in society can be seen in the context of accelerated development of information and communication technologies. The Information becomes more fluid and accessible, and with it, the cultural production of the contemporary man, if culture is taken as the production of the everyday objects and processes (as points out Vilém Flusser and Sharon Zukin). The museum, in turn, as an institution that represents society, tries to adapt itself as virtual museums among other names. For that, it houses such technologies as well as it projects itself onto the Internet. At the same time, the proponents of these museums allege that it has more interaction, accompanying the tendencies of the society itself. The use of computer, mobile phones, sensors and GPS, among others, is considered a key factor of this new human condition of being always online. The aim of this dissertation was to investigate museums in the current virtual and interactive context. The motivation for such a research was the impression that the contemporary museum is not more interactive just because it has adapted itself to the contemporary technological context. Similarly, the use of the word virtual is misplaced, or at least misleading, because it is based on the electronic production of content. Therefore, theories of second order cybernetics were used as a framework to evaluate some museum that use such an approach. Different strategies that illustrate the physical-digital spam were selected, i.e. physical museums that use technologies as part of their collection as well as those that have created an online version of themselves, and those which have been designed only for the Internet. From the analysis of those different strategies, it is possible to conclude that the museum has not in fact adapted to the new demands of society. Although the institution uses technological means to produce content or even itself, it has not absorbed other changes that go beyond the means of production towards different relationships among people. The new technologies give us the possibility to use the museum as the place of mutual discoveries through interactions of people with themselves, the space and the work, but it is not what usually happens. Generally, the museum is still attached to traditionalist precepts, such as authorship, restrictive control and deterministic architecture. A proof of that is the importance given to architectural parameters of the museum even when a embodied engagement to such space is impossible. To conclude, a discussion of other alternative cultural approaches have been presented in order to suggest that we can benefit from other institutions that explore the possibilities of architecture and ephemeral encounters while considering the virtualities that enable interaction among people, place and cultural/artistic production as dialogues in the space. These proposed museums can be called Beta Museums, for their experimental and mutable character, always in process of development.